GRK2 inhibitors, paroxetine and CCG258747, attenuate IgE-mediated anaphylaxis but activate mast cells via MRGPRX2 and MRGPRB2 - Thapaliya, Monica; Amponnawarat, Aetas; Tesmer, John J. G.; Ali, Hydar (Frontiers in Immunology, 2022)
G protein-coupled receptor (GPCR) kinase 2 (GRK2), which phosphorylates agonist-occupied GPCRs to promote their desensitization, has been investigated as an attractive therapeutic target for cardiovascular and metabolic diseases. Several GRK2-targeted inhibition strategies have been reported including the use of direct pharmacological inhibitors such as paroxetine (a widely prescribed antidepressant) and its analogs such as compound CCG258747. Cross-linking of high affinity IgE receptor (FcεRI) on mast cells (MCs) and the resulting degranulation causes anaphylaxis and allergic asthma. Using gene silencing strategy, we recently showed that GRK2 contributes to FceRI signaling and MC degranulation. The purpose of this study was to determine if the GRK2 inhibitors paroxetine and CCG258747 modulate FceRI-mediated MC responses in vitro and in vivo. Utilizing rat basophilic leukemia (RBL-2H3) cells and primary mouse lung MCs (LMCs), we found that paroxetine and CCG258747 inhibit FcεRI-mediated calcium mobilization and degranulation. Furthermore, intravenous administration of paroxetine and CCG258747 in mice resulted in substantial reduction of IgE-mediated passive cutaneous anaphylaxis. Unlike LMCs, human cutaneous MCs abundantly express a novel GPCR known as MRGPRX2 (mouse; MRGPRB2). We found that in contrast to their inhibitory effects on FceRI-mediated MC responses, both paroxetine and CCG258747 induce calcium mobilization and degranulation in RBL-2H3 cells stably expressing MRGPRX2 but not in untransfected cells. Furthermore, paroxetine and CCG258747 induced degranulation in peritoneal MCs from Wild-type (WT) mice in vitro and caused increased cutaneous vascular permeability in vivo, but these responses were substantially reduced in Mrgprb2−/− mice. Additionally, upon intradermal injection, paroxetine also induced neutrophil recruitment in WT but not Mrgprb2−/− mice. These findings suggest that in addition to their potential therapeutic utility against cardiovascular and metabolic disorders, paroxetine-based GRK2-inhibitors may serve to modulate IgE-mediated anaphylaxis and to enhance cutaneous host defense by harnessing MC’s immunomodulatory property through the activation of MRGPRX2/MRGPRB2.